A-DANZAR propuesta didáctica para la enseñanza de la pre-danza en niños de 6 a 9 años de edad a partir del juego (2021)
The A-DANZAR primer is a proposal for the creation of didactic material aimed at boys and girls from 6 to 9 years of age whose objective is the development and appropriation of three physical abilities, such as the body scheme, laterality and corporal expression, the which are considered important for a pre-dance process; in this way, the game is used as a learning tool and in turn, it is sought to arrive at a compendium with these skills to create a pre-dance proposal